Biochemical characterization and pharmacological properties of a phospholipase A2 myotoxin inhibitor from the plasma of the snake Bothrops asper - Lizano González, Sergio (1997)
A protein that neutralizes the biological activities of basic phospholipase A2 (PLA2) myotoxin isoforms from the venom of the snake Bothrops asper was isolated from its blood by affinity chromatography with Sepharose-immobilized myotoxins. Biochemical characterization of this B. asper myotoxin inhibitor protein (BaMIP) indicated a subunit molecular mass of 23-25 kDa, an isoelectric point of 4, and glycosylation. Gel-filtration studies revealed a molecular mass of 120 kDa, suggesting that BaMIP possesses an oligomeric structure composed of five 23-25 kDa subunits. Functional studies indicated that BaMIP inhibits the PLA2 activity of B. asper basic myotoxins I and III, as well as the myotoxicity and edema-forming activity in vivo and cytolytic activity in vitro towards cultured endothelial cells, of all four myotoxin isoforms (I-IV) tested. Sequence analysis of the first 63 amino acid residues from the N-terminus of BaMIP indicated more than 65% sequence similarity to the PLA2 inhibitors isolated from the blood of the crotalid snakes Trimeresurus flavoviridis and Agkistrodon blomhoffii siniticus. These inhibitors also share sequences similar to the carbohydrate-recognition domains of human and rabbit cellular PLA2 receptors, suggesting a common domain evolution among snake plasma PLA2 inhibitors and mammalian PLA2 receptors. Despite this similarity, this is the first description of a natural anti-myotoxic factor from snake blood.